Novel Strategies for Applied Metagenomics. Issue 3 (March 2016) - Moore-Connors, Jessica M.; Dunn, Katherine A.; Bielawski, Joseph P.; Van Limbergen, Johan
Abstract : Abstract: Detailed analyses of the gut microbiome and its effect on human physiology and disease are emerging, thanks to advances in high-throughput DNA-sequencing technology and the burgeoning field of metagenomics. Metagenomics examines the structure and functional potential of microbial communities in their native habitats through the direct isolation and analysis of community DNA. In inflammatory bowel disease, gut microbiome studies have shown an association with perturbations in community composition and, especially, function. In this review, we discuss the application of next-generation sequencing to microbiome research and highlight the importance of modeling microbiome structure and function to the future of inflammatory bowel disease research and treatment. Abstract : Article first published online 5 February 2016.